Flat nanofiltration membrane and preparation method thereof
By introducing heavy metals and micro -pollutants to remove layers in the nanofilled membrane, the chemical reaction layer of amino and polyester support layers is used to form a adsorption layer, which solves the problem of decreased flux and low efficiency during use during use, and achieved it. Efficient removal of heavy metals and micro -pollutants and the preservation of minerals.
Patent Information
- Application Number
- CN202310888799.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
During use, nanofiltration membranes are prone to decrease flux due to membrane pollution, which cannot effectively remove heavy metals and micro-contaminants in the water, and can also remove mineral elements that are beneficial to the human body.
A new type of flat plate filter membrane that includes a separatist layer, tablet ultra -filter film and heavy metal and micro pollutants. The removal layer of heavy metals and micro -pollutants via the chemical reaction of the amino group and polyester support layer on the tablet ultra -filter membrane, forming a adsorption layer with efficient removal of performance.
The efficient removal of heavy metals and micro -pollutants has been achieved, and the removal of minerals is avoided, and the flux and life of the membrane are improved.
Abstract
Description
Technical Field
[0001] The invention relates to a flat nanofiltration membrane and a preparation method thereof. Background Art
[0002] Tap water contains heavy metal ions and micropollutants at the ppb level. Long-term drinking of water containing heavy metal ions and micropollutants will cause heavy metals and micropollutants to accumulate in human organs, which is extremely harmful to the human body. Therefore, the less heavy metal ions and micropollutants contained in drinking water, the better. At present, membrane methods, ion exchange, electrodialysis and activated carbon separation are generally used to remove heavy metal ions and micropollutants. The most common method is to use reverse osmosis filter elements. While reverse osmosis removes heavy metals and micropollutants, it also removes mineral elements that are beneficial to the human body. Nanofiltration filter elements have a certain effect on removing heavy metals and micropollutants while retaining minerals in the water, but they cannot completely remove heavy metals in the water. Other methods for removing heavy metals and micropollutants, such as ion exchange, electrodialysis and activated carbon separation, have problems such as poor removal effect and high cost.
[0003] Nanofiltration membrane is a new type of separation membrane developed in the 1980s. It is a membrane separation technology between ultrafiltration and reverse osmosis. The molecular weight cutoff is between 200 and 1000 Da. It has a high retention effect on various organic pollutants, such as chloroform intermediates, pesticides, hormones, small molecular organic matter, etc., and has a high retention effect on inorganic ions, such as Ca 2+ 、F - , Cl - 、SO 4 2- , heavy metal ions, etc. can be removed moderately, and can be widely adapted to water source requirements and water purification applications. Nanofiltration membrane has become one of the important water purification technologies due to its special selective separation performance. Nanofiltration has a high efficiency in removing trace organic matter and heavy metals. With the decline in the cost of membrane components, nano-membranes show broad application prospects.
[0004] However, nanofiltration membranes will face membrane pollution problems during use. Inorganic and organic matter in the water will be deposited at the membrane pores, resulting in blockage of the air ports, membrane surface pollution, increased operating pressure, and decreased membrane flux. Nanofiltration membrane pollution mainly includes organic pollution, inorganic pollution, colloidal particle pollution, and biological pollution. The corresponding pollutants mainly include organic solutes, inorganic solutes, colloids, and biological solid substances. Among them, inorganic pollution is Ca in water. 2+ Mg 2+ 、Al 3+ , Fe 2+ , Ba 2+Plasma scales on the membrane surface, causing membrane blockage. Studies have found that the higher the concentration of biodegradable organic matter in the influent of the nanofiltration membrane process, the faster the biofilm forms, and the membrane surface pollution comes from the synergistic effect of organic, inorganic and biological pollution. The membrane pollution phenomenon has seriously restricted the application of nanofiltration membranes in drinking water treatment.
[0005] Therefore, how to effectively remove heavy metals and micropollutants through nanofiltration membranes while preventing the membrane flux from being reduced due to adsorption is an urgent problem to be solved in the prior art. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a novel flat nanofiltration membrane having the performance of removing heavy metals and micro-pollutants and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] One of the technical solutions provided by the present invention is: a flat nanofiltration membrane, characterized in that the flat nanofiltration membrane includes a separation layer, a flat ultrafiltration membrane and a heavy metal and micro-pollutant removal layer, the flat ultrafiltration membrane includes a base membrane and a polyester support layer, one outer surface of the polyester support layer is arranged in close contact with the base membrane, and the other outer surface is connected to the heavy metal and micro-pollutant removal layer; the polyester support layer and the heavy metal and micro-pollutant removal layer are connected through an amide bond; the separation layer is located at the outermost side of the flat nanofiltration membrane and is arranged in close contact with the base membrane.
[0009] In the present invention, the flat nanofiltration membrane also satisfies one or more of the following conditions:
[0010] a. The separation layer satisfies one or more of the following conditions:
[0011] ① The thickness of the separation layer is 10 to 200 nm, for example, 50 nm, 100 nm;
[0012] ② The separation pore size of the separation layer is 0.5 to 5 nm, for example, 1 nm, 2 nm or 3 nm;
[0013] ③ The material of the separation layer is polyamide;
[0014] b. The main material of the base film is one or more of polysulfone, polyethersulfone, polypropylene and polyvinyl chloride;
[0015] c. The thickness of the base film is 50 to 200 μm, for example, 50 μm, 100 μm or 200 μm;
[0016] d. The material of the polyester support layer is polyethylene terephthalate and / or polybutylene terephthalate;
[0017] e. The thickness of the polyester support layer is 10 to 100 μm, for example, 10 μm, 50 μm or 100 μm;
[0018] f. The thickness of the heavy metal and micro-pollutant removal layer is 50 to 1000 nm, for example, 100 nm, 200 nm, 300 nm or 800 nm;
[0019] g. The material of the heavy metal and micro-pollutant removal layer is a reactant of an amine substance and β-cyclodextrin. Preferably, the amine substance is one or more of chitosan, polyethyleneimine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine. More preferably, the amine substance is polyethyleneimine or chitosan.
[0020] The second technical solution provided by the present invention is: a method for preparing a flat nanofiltration membrane, comprising the following steps: (1) preparing an amino-containing heavy metal and micropollutant removal layer: adding β-cyclodextrin and ethylenediaminetetraacetic acid and / or oxalic acid to an aqueous solution for reaction, then adding an amine substance and continuing the reaction; wherein the β-cyclodextrin and the amine substance respectively meet one or two of the following conditions:
[0021] a. The concentration of β-cyclodextrin in the aqueous solution is 1-10wt%;
[0022] b. The concentration of the amine substance is 1-10wt%;
[0023] (2) Immersing a flat ultrafiltration membrane comprising a base membrane and a polyester support layer in a solution of the amino-containing heavy metal and micropollutant removal layer to react, and then subjecting the flat nanofiltration membrane to interfacial polymerization to form a separation layer on the base membrane; in the flat ultrafiltration membrane, an outer surface of the polyester support layer is disposed in close contact with the base membrane.
[0024] The step (2) satisfies one or both of the following conditions:
[0025] a. The reaction temperature is 60-90°C, for example 60°C, 80°C or 90°C;
[0026] b. The reaction time is 5-15 h, for example 6 h, 8 h or 15 h.
[0027] Wherein, the step (1) satisfies one or more of the following conditions:
[0028] a. The concentration of β-cyclodextrin in the aqueous solution is 1wt%, 2wt% or 8wt%;
[0029] b. The concentration of EDTA in the aqueous solution is 0.006wt%-0.06wt%, such as 0.012wt%, 0.049wt% or 0.006wt%;
[0030] c. The concentration of oxalic acid in the aqueous solution is 0.004wt%;
[0031] d. The molar ratio of β-cyclodextrin to ethylenediaminetetraacetic acid is 42:1;
[0032] e. The molar ratio of β-cyclodextrin to oxalic acid is 42:1;
[0033] f. The reaction temperature is 40-80°C, such as 40°C, 50°C or 80°C;
[0034] g. The reaction time is 1-8 h, for example 1 h, 6 h or 7.5 h;
[0035] h. The amine substance is one or more of chitosan, polyethyleneimine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, preferably polyethyleneimine or chitosan;
[0036] i. The concentration of the amine substance is 2wt%, 4wt% or 6wt%;
[0037] j. The reaction time is 0.5-3 h, for example 0.5 h, 1 h or 3 h.
[0038] In the step (2), after the reaction, the flat nanofiltration membrane is cleaned and dried;
[0039] Preferably, the cleaning is to soak the flat nanofiltration membrane in pure water;
[0040] More preferably, the soaking operation satisfies one or both of the following conditions:
[0041] a. The soaking time is 5-24 hours, for example 8 hours, 10 hours or 20 hours;
[0042] b. The soaking temperature is 20-60°C, such as 20°C, 40°C or 50°C.
[0043] Preferably, the drying satisfies one or two of the following conditions:
[0044] a. The drying temperature is 20-35°C, for example 25°C, 30°C or 35°C;
[0045] b. The drying time is 48-72 hours, for example 50 hours, 65 hours or 70 hours;
[0046] In the step (2), the separation layer is formed by the reaction of piperazine and trimesoyl chloride.
[0047] The interfacial polymerization reaction comprises the following steps:
[0048] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0049] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0050] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0051] d. Pour about 15 mL of the prepared n-hexane solution with trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. Let it react for 30 seconds and pour the oil phase into the waste liquid bucket.
[0052] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven at 80°C for 20 seconds.
[0053] The thickness of the obtained interfacial polymerization separation layer is 100 nm, and the separation pore diameter is 2 nm.
[0054] In the present invention, the preparation method further comprises washing, moisturizing and drying the membrane sheet forming the separation layer to obtain the flat nanofiltration membrane, wherein the washing process is to soak the membrane sheet forming the separation layer in pure water;
[0055] Preferably, the process of washing, moisturizing and drying the membrane forming the separation layer satisfies one or more of the following conditions:
[0056] a. The soaking time is 5-24 hours, for example 15 hours, 16 hours or 24 hours;
[0057] b. The soaking temperature is 20-60°C, for example 20°C, 30°C or 50°C;
[0058] c. In the moisturizing process, the moisturizing agent is one or more of glycerin, sodium lactate, potassium lactate, and sodium citrate, preferably sodium lactate or glycerin;
[0059] d. The drying temperature is 20-35°C, for example 20°C, 25°C or 35°C;
[0060] e. The drying time is 48-72 hours, for example 48 hours, 60 hours or 70 hours.
[0061] The third technical solution provided by the present invention is: a flat nanofiltration membrane prepared by the method for preparing the flat nanofiltration membrane as described above.
[0062] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0063] The reagents and raw materials used in the present invention are commercially available.
[0064] The positive and progressive effects of the present invention are:
[0065] The adsorbent with heavy metal and micro-pollutant adsorption performance is grafted onto the flat ultrafiltration membrane through the chemical reaction of amino group and polyester support layer, which makes the combination more firm. Therefore, the removal effect of the membrane is efficient and stable, and the service life is long. The heavy metal adsorption performance of the flat nanofiltration membrane is tested. The Cd(NO 3 )2 concentration is less than or equal to 5ppb, and the final amount of water in the spiked solution passing through the membrane can reach up to 7.1L; the flat nanofiltration membrane is tested for its micro-pollutant adsorption performance, and the concentration of bisphenol A (BPA) passing through the membrane is less than or equal to 10ppb, and the final amount of water in the spiked solution passing through the membrane can reach up to 8.8L. DETAILED DESCRIPTION
[0066] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0067] The flat ultrafiltration membranes in all the following examples and comparative examples are prepared by scraping the base membrane raw material onto a polyester support layer by a scraper, and the polyester support layer is prepared by a melt-blowing-hot rolling process.
[0068] Example 1
[0069] (1) Add β-cyclodextrin and ethylenediaminetetraacetic acid to an aqueous solution, wherein the concentration of β-cyclodextrin is 2wt%, the concentration of tetraethylammonium oxalate is 0.012wt%, the molar ratio of β-cyclodextrin to ethylenediaminetetraacetic acid is 42:1, the reaction temperature is 50°C, and the reaction time is 6h. Then, polyimide is added at a concentration of 4wt%, and the reaction is continued for 1h;
[0070] (2) placing a flat ultrafiltration membrane containing a base membrane whose main material is polyethersulfone and whose thickness is 100 μm and a polyester support layer whose material is polyethylene terephthalate and whose thickness is 10 μm into the solution of step (1), adjusting the temperature to 80° C., reacting for 8 hours, and forming a heavy metal and micropollutant removal layer with a thickness of 200 nm at the bottom of the polyester support layer;
[0071] (3) Soaking the flat ultrafiltration membrane after the reaction in 20° C. pure water, changing the water every hour, soaking for 20 hours, taking it out, drying it at 25° C. for 70 hours, and then performing interfacial polymerization reaction on the ultrafiltration layer to form a separation layer;
[0072] The interfacial polymerization reaction comprises the following steps:
[0073] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0074] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0075] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0076] d. Pour about 15 mL of the prepared n-hexane solution with trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. Let it react for 30 seconds and pour the oil phase into the waste liquid bucket.
[0077] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven at 80°C for 20 seconds.
[0078] The thickness of the obtained interfacial polymerization separation layer is 100 nm, and the separation pore diameter is 2 nm.
[0079] (4) Soaking the membrane obtained in step (3) in 30° C. pure water, changing the water every hour, and soaking for 15 hours; after washing, placing it in an aqueous solution of sodium lactate for moisturizing, and finally drying it at 25° C. for 60 hours to obtain a new flat nanofiltration membrane with the ability to remove heavy metals and micropollutants;
[0080] (5) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. 3 ) 2 ) solution as the spike solution. When the solution passing through the membrane, Cd(NO 3 ) 2 When the concentration is greater than 5ppb, the test is stopped, and the final amount of water in the membrane that passes through the spiked solution is 4.3L; the above test shows that when the cut-off concentration reaches 5ppb, the amount of water in the membrane that passes through the spiked solution can reach 4.3L.
[0081] (6) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spike solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the spike solution of the membrane was 5.6 L. The above test shows that when the cut-off concentration reaches 10 ppb, the amount of water passing through the spike solution of the membrane can reach 5.6 L.
[0082] Example 2
[0083] (1) β-cyclodextrin and ethylenediaminetetraacetic acid were added to an aqueous solution, the concentration of β-cyclodextrin was 8wt%, the concentration of tetraethylammonium oxalate was 0.049wt%, the molar ratio of β-cyclodextrin to ethylenediaminetetraacetic acid was 42:1, the reaction temperature was 80°C, and the reaction time was 1h. Chitosan was then added at a concentration of 6wt%, and the reaction was continued for 0.5h;
[0084] (2) placing a flat ultrafiltration membrane containing a base membrane whose main material is polysulfone and whose thickness is 50 μm and a polyester support layer whose material is polyethylene terephthalate and whose thickness is 50 μm into the solution of step (1), adjusting the temperature to 60° C., reacting for 15 h, and forming a heavy metal and micropollutant removal layer with a thickness of 800 nm at the bottom of the polyester support layer;
[0085] (3) Soaking the flat ultrafiltration membrane after the reaction in 40° C. pure water, changing the water every hour, soaking for 10 hours, taking it out, drying it at 30° C. for 65 hours, and then performing interfacial polymerization reaction on the ultrafiltration layer to form a separation layer;
[0086] The interfacial polymerization reaction comprises the following steps:
[0087] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0088] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0089] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0090] d. Pour about 15 mL of the prepared n-hexane solution with trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. Let it react for 20 seconds and pour the oil phase into the waste liquid bucket.
[0091] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven to react at 80°C for 20 seconds.
[0092] The thickness of the obtained interfacial polymerization separation layer is 50 nm, and the separation pore diameter is 3 nm.
[0093] (4) Soaking the membrane obtained in step (3) in pure water at 20° C., changing the water every hour for 24 hours; after washing, placing it in a glycerol aqueous solution for moisturizing, and finally drying it at 35° C. for 48 hours to obtain a novel flat nanofiltration membrane with the ability to remove heavy metals and micropollutants;
[0094] (5) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. 3 ) 2 ) solution as the spike solution. When the solution passing through the membrane, Cd(NO 3 ) 2 When the concentration is greater than 5ppb, the test is stopped, and the final amount of water in the membrane that passes through the spiked solution is 7.1L; the above test shows that when the cut-off concentration reaches 5ppb, the amount of water in the membrane that passes through the spiked solution can reach 7.1L.
[0095] (6) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spike solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the spike solution of the membrane was 8.8 L. The above test shows that when the cut-off concentration reaches 10 ppb, the amount of water passing through the spike solution of the membrane can reach 8.8 L.
[0096] Example 3
[0097] (1) Add β-cyclodextrin and ethylenediaminetetraacetic acid to an aqueous solution, the concentration of β-cyclodextrin is 1wt%, the concentration of tetraethylammonium oxalate is 0.006wt%, the molar ratio of β-cyclodextrin to ethylenediaminetetraacetic acid is 42:1, the reaction temperature is 40°C, and the reaction time is 7.5h. Then add chitosan at a concentration of 2wt% and continue the reaction for 3h;
[0098] (2) placing a flat ultrafiltration membrane containing a main material of polysulfone with a thickness of 200 μm and a polyester support layer of polybutylene terephthalate with a thickness of 100 μm into the solution of step (1), adjusting the temperature to 90° C., reacting for 6 hours, and forming a heavy metal and micropollutant removal layer with a thickness of 100 nm at the bottom of the polyester support layer;
[0099] (3) Soaking the flat ultrafiltration membrane after the reaction in 50° C. pure water, changing the water every hour, soaking for 8 hours, taking it out, drying it at 35° C. for 50 hours, and then performing interfacial polymerization reaction on the ultrafiltration layer to form a separation layer;
[0100] The interfacial polymerization reaction comprises the following steps:
[0101] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0102] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0103] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0104] d. Pour about 15 mL of the prepared n-hexane solution of trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. React for 40 seconds and pour the oil phase into the waste liquid bucket;
[0105] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven at 80°C for 20 seconds.
[0106] The thickness of the obtained interfacial polymerization separation layer is 100 nm, and the separation pore diameter is 1 nm.
[0107] (4) Soaking the membrane obtained in step (3) in 50° C. pure water, changing the water every hour, and soaking for 16 hours; after washing, placing it in a glycerol aqueous solution for moisturizing, and finally drying it at 20° C. for 70 hours to obtain a new flat nanofiltration membrane with the ability to remove heavy metals and micropollutants;
[0108] (5) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. 3 ) 2 ) solution as the spike solution. When the solution passing through the membrane, Cd(NO 3 ) 2 When the concentration is greater than 5ppb, the test is stopped, and the final amount of water in the membrane that passes through the spiked solution is 2.9L; the above test shows that when the cut-off concentration reaches 5ppb, the amount of water in the membrane that passes through the spiked solution can reach 2.9L.
[0109] (6) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spike solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. Finally, the amount of water passing through the spike solution of the membrane was 3.5 L. The above test shows that when the cut-off concentration reaches 10 ppb, the amount of water passing through the spike solution of the membrane can reach 3.5 L.
[0110] Example 4
[0111] (1) Add β-cyclodextrin and oxalic acid to an aqueous solution, the concentration of β-cyclodextrin is 2wt%, the concentration of oxalic acid is 0.004wt%, the molar ratio of β-cyclodextrin to oxalic acid is 42:1, the reaction temperature is 50°C, and the reaction time is 6h. Then add polyacetimide at a concentration of 4wt% and continue the reaction for 1h;
[0112] (2) placing a flat ultrafiltration membrane containing a base membrane whose main material is polyethersulfone and whose thickness is 100 μm and a polyester support layer whose material is polyethylene terephthalate and whose thickness is 10 μm into the solution of step (1), adjusting the temperature to 80° C., reacting for 8 hours, and forming a heavy metal and micropollutant removal layer with a thickness of 300 nm at the bottom of the polyester support layer;
[0113] (3) Soaking the flat ultrafiltration membrane after the reaction in 20° C. pure water, changing the water every hour, soaking for 20 hours, taking it out, drying it at 25° C. for 70 hours, and then performing interfacial polymerization reaction on the ultrafiltration layer to form a separation layer;
[0114] The interfacial polymerization reaction comprises the following steps:
[0115] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0116] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0117] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0118] d. Pour about 15 mL of the prepared n-hexane solution with trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. Let it react for 30 seconds and pour the oil phase into the waste liquid bucket.
[0119] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven at 80°C for 20 seconds.
[0120] The thickness of the obtained interfacial polymerization separation layer is 100 nm, and the separation pore diameter is 2 nm.
[0121] (4) Soaking the membrane obtained in step (3) in 30° C. pure water, changing the water every hour, and soaking for 15 hours; after washing, placing it in an aqueous solution of sodium lactate for moisturizing, and finally drying it at 25° C. for 60 hours to obtain a new flat nanofiltration membrane with the ability to remove heavy metals and micropollutants;
[0122] (5) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. 3 ) 2 ) solution as the spike solution. When the solution passing through the membrane, Cd(NO 3 ) 2If the concentration is greater than 5ppb, the test is stopped, and the final amount of water in the membrane that passes through the spiked solution is 3.5L; the above test shows that when the cut-off concentration reaches 5ppb, the amount of water in the membrane that passes through the spiked solution can reach 3.5L.
[0123] (6) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spike solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the spike solution of the membrane was 4.1 L. The above test shows that when the cut-off concentration reaches 10 ppb, the amount of water passing through the spike solution of the membrane can reach 4.1 L.
[0124] Comparative Example 1
[0125] (1) Interfacial polymerization reaction occurs on the surface of the flat ultrafiltration membrane to form a separation layer;
[0126] The interfacial polymerization reaction comprises the following steps:
[0127] a. Place the flat ultrafiltration membrane in a plexiglass frame, clamp it with a clip, and place it upright in a fume hood. Wait for the water on the membrane surface to evaporate for about 10 minutes.
[0128] b. Pour about 30 mL of the prepared aqueous solution of piperazine into the plexiglass frame, try to pour it from the corner of the plexiglass frame, and let it stand for 5 minutes;
[0129] c. Pour the water phase into the waste liquid bucket, then stand the membrane upright and wait for the water phase to evaporate completely for about 3 minutes;
[0130] d. Pour about 15 mL of the prepared n-hexane solution with trimesoyl chloride as the oil phase into the plexiglass frame. It must be poured from the corner of the plexiglass frame. Let it react for 30 seconds and pour the oil phase into the waste liquid bucket.
[0131] e. Shake the membrane vigorously to evaporate the oil phase quickly, and place it in an oven at 80°C for 20 seconds.
[0132] The thickness of the obtained interfacial polymerization separation layer is 100 nm, and the separation pore size is 2 nm.
[0133] (2) soaking the membrane obtained in step (1) in pure water at 30° C., changing the water every hour, and soaking for 15 hours; after washing, placing it in an aqueous solution of sodium lactate for moisturizing, and finally drying it at 25° C. for 60 hours to obtain a novel flat nanofiltration membrane with partial removal performance but a removal rate of less than 80%;
[0134] (3) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. 3) 2 ) solution as the spike solution. When the solution passing through the membrane, Cd(NO 3 ) 2 When the concentration is greater than 5ppb, the test is stopped. Finally, the amount of water in the membrane that passes through the spiked solution is 0L. Cd (NO 3 ) 2 The concentration was always kept at 8 ppb;
[0135] (4) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spiked solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. Finally, the amount of water passing through the spiked solution of the membrane was 0 L, and the BPA concentration detected in the solution passing through the membrane was always maintained at 23 ppb.
Claims
1. A flat nanofiltration membrane, characterized in that: The flat nanofiltration membrane includes a separation layer, a flat ultrafiltration membrane and a heavy metal and micro-pollutant removal layer. The flat ultrafiltration membrane includes a base membrane and a polyester support layer. One outer surface of the polyester support layer is arranged in close contact with the base membrane, and the other outer surface is connected to the heavy metal and micro-pollutant removal layer; the polyester support layer and the heavy metal and micro-pollutant removal layer are connected through an amide bond; the separation layer is located at the outermost side of the flat nanofiltration membrane and is arranged in close contact with the base membrane.
2. The flat nanofiltration membrane according to claim 1, characterized in that The flat nanofiltration membrane meets one or more of the following conditions: a. The separation layer satisfies one or more of the following conditions: ① The thickness of the separation layer is 10 to 200 nm, for example, 50 nm, 100 nm; ② The separation pore size of the separation layer is 0.5 to 5 nm, for example, 1 nm, 2 nm or 3 nm; ③ The material of the separation layer is polyamide; b. The main material of the base film is one or more of polysulfone, polyethersulfone, polypropylene and polyvinyl chloride; c. The thickness of the base film is 50 to 200 μm, for example, 50 μm, 100 μm or 200 μm; d. The material of the polyester support layer is polyethylene terephthalate and / or polybutylene terephthalate; e. The thickness of the polyester support layer is 10 to 100 μm, for example, 10 μm, 50 μm or 100 μm; f. The thickness of the heavy metal and micro-pollutant removal layer is 50 to 1000 nm, for example, 100 nm, 200 nm, 300 nm or 800 nm; g. The material of the heavy metal and micro-pollutant removal layer is a reactant of an amine substance and β-cyclodextrin. Preferably, the amine substance is one or more of chitosan, polyethyleneimine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine. More preferably, the amine substance is polyethyleneimine or chitosan.
3. A method for preparing a flat nanofiltration membrane, characterized in that: The steps include: (1) Preparation of a heavy metal and micropollutant removal layer containing an amino group: β-cyclodextrin and ethylenediaminetetraacetic acid and / or oxalic acid are added to an aqueous solution for reaction, and then an amine substance is added to continue the reaction; wherein the β-cyclodextrin and the amine substance respectively meet one or two of the following conditions: a. The concentration of β-cyclodextrin in the aqueous solution is 1-10wt%; b. The concentration of the amine substance is 1-10wt%; (2) Immersing a flat ultrafiltration membrane comprising a base membrane and a polyester support layer in a solution of the amino-containing heavy metal and micropollutant removal layer to react, and then subjecting the flat nanofiltration membrane to interfacial polymerization to form a separation layer on the base membrane; in the flat ultrafiltration membrane, an outer surface of the polyester support layer is disposed in close contact with the base membrane.
4. The method for preparing a flat nanofiltration membrane according to claim 3, characterized in that: The step (2) satisfies one or both of the following conditions: a. The reaction temperature is 60-90°C, for example 60°C, 80°C or 90°C; b. The reaction time is 5-15 h, for example 6 h, 8 h or 15 h.
5. The method for preparing a flat nanofiltration membrane according to claim 3, characterized in that: The step (1) satisfies one or more of the following conditions: a. The concentration of β-cyclodextrin in the aqueous solution is 1wt%, 2wt% or 8wt%; b. The concentration of EDTA in the aqueous solution is 0.006wt%-0.06wt%, such as 0.012wt%, 0.049wt% or 0.006wt%; c. The concentration of oxalic acid in the aqueous solution is 0.004wt%; d. The molar ratio of β-cyclodextrin to ethylenediaminetetraacetic acid is 42:1; e. The molar ratio of β-cyclodextrin to oxalic acid is 42:1; f. The reaction temperature is 40-80°C, such as 40°C, 50°C or 80°C; g. The reaction time is 1-8 h, for example 1 h, 6 h or 7.5 h; h. The amine substance is one or more of chitosan, polyethyleneimine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, preferably polyethyleneimine or chitosan; i. The concentration of the amine substance is 2wt%, 4wt% or 6wt%; j. The reaction time is 0.5-3 h, for example 0.5 h, 1 h or 3 h.
6. The method for preparing a flat nanofiltration membrane according to claim 3, characterized in that: In the step (2), after the reaction, the flat nanofiltration membrane is cleaned and dried. Preferably, the cleaning is to soak the flat nanofiltration membrane in pure water; More preferably, the soaking operation satisfies one or both of the following conditions: a. The soaking time is 5-24 hours, for example 8 hours, 10 hours or 20 hours; b. The soaking temperature is 20-60°C, such as 20°C, 40°C or 50°C.
7. The method for preparing a flat nanofiltration membrane according to claim 6, characterized in that: The preparation method meets one or more of the following conditions: a. The drying temperature is 20-35°C, for example 25°C, 30°C or 35°C; b. The drying time is 48-72 hours, for example 50 hours, 65 hours or 70 hours.
8. The method for preparing a flat nanofiltration membrane according to claim 3, characterized in that: In the step (2), the separation layer is formed by the reaction of piperazine and trimesoyl chloride, and the step further comprises washing, moisturizing and drying the membrane sheet forming the separation layer to obtain a flat nanofiltration membrane, wherein the washing process is to soak the membrane sheet forming the separation layer in pure water; Preferably, the process of washing, moisturizing and drying the membrane forming the separation layer satisfies one or more of the following conditions: a. The soaking time is 5-24 hours, for example 15 hours, 16 hours or 24 hours; b. The soaking temperature is 20-60°C, for example 20°C, 30°C or 50°C; c. In the moisturizing process, the moisturizing agent is one or more of glycerin, sodium lactate, potassium lactate, and sodium citrate, preferably sodium lactate or glycerin; d. The drying temperature is 20-35°C, for example 20°C, 25°C or 35°C; e. The drying time is 48-72 hours, for example 48 hours, 60 hours or 70 hours.
9. A flat nanofiltration membrane obtained by the method for preparing a flat nanofiltration membrane according to any one of claims 3 to 8.
Citation Information
Patent Citations
Cyclodextrin modified composite organic solvent nanofiltration membrane and preparation method thereof
CN104128102A
Composite nanofiltration film and preparation method thereof
CN110917897A
Tannic acid-hydroxypropyl beta cyclodextrin composite nanofiltration membrane and preparation method thereof
CN113457468A
Anode actine material conprising polydopamine coating layer for secondary battery and method for preparing the same
KR102219161B1
Porous nanocomposite polymers for water treatment
US20150353381A1
Cited By
Preparation method of high-power concentrated SD diaphragm and high-power concentrated SD diaphragm
CN122076251A